Therapeutic Benefits of Tocilizumab Vary in Different Organs of a Patient with AA Amyloidosis. (12th August 2014) - Matsui, Masaru; Okayama, Satoshi; Tsushima, Hideo; Samejima, Kenichi; Kanki, Tomoko; Hasegawa, Ayako; Morimoto, Katsuhiko; Akai, Yasuhiro; Takano, Masato; Uemura, Shiro; Ohbayashi, Chiho; Saito, Yoshihiko
Abstract : Systemic reactive AA amyloidosis is a life-threatening complication of chronic inflammatory diseases. Anti-interleukin-6 receptor, tocilizumab (TCZ), has been shown to improve clinical symptoms of patients with AA amyloidosis, accompanied with regression of the amyloid deposition. We report a case of AA amyloidosis evaluated by histology of multiple organs before and after TCZ treatment. A woman in her 60s with rheumatoid arthritis was referred to our hospital because of cardiac and renal dysfunction. A gastric and renal biopsy revealed the deposition of AA amyloid, and echocardiography revealed concentric left ventricular hypertrophy. Her estimated glomerular filtration rate was decreased to 8.6 mL/min/1.73 m 2, and B-type natriuretic peptide, C-reactive protein, and serum amyloid A protein were significantly elevated. TCZ treatments markedly decreased her serum amyloid A protein and C-reactive protein levels, but hemodialysis was required 1 year later. Endoscopic gastric rebiopsy 3 years after initiation of TCZ treatments revealed the regression of amyloid deposition and echocardiography revealed improvement of her left ventricular hypertrophy. However, a renal rebiopsy revealed that the amyloid deposition had not regressed. In conclusion, these observations suggest that the therapeutic effects of TCZ can vary among organs in patients with AA amyloidosis.